2008
DOI: 10.1007/s10704-008-9271-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent scheme for toughness homogenization

Abstract: Considering a semi-infinite planar crack propagating along a plane where the local toughness is a random field, the addressed problem is to compute the effective (or homogeneous and macroscopic) toughness. After a brief introduction to the two regimes-strong and weak pinning-that are expected depending on the system size, a self-consistent homogenization scheme is introduced. It is shown that this scheme allows one to predict not only the mean value but also the standard deviation and even the complete probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…Fig.7-B shows the PDF of E dep for experiment I at strain S b when an avalanche is triggered. This energy is sometimes called the depinning energy, and in the framework of the pinning-depinning theory, several models predict Gaussian statistics [47][48][49][50]. In our case, unlike these models, we observe a power-law distribution, and the measured experimental exponent is close to 1: γ = −1.08 ± 0.1.…”
Section: A Global Avalanchessupporting
confidence: 39%
“…Fig.7-B shows the PDF of E dep for experiment I at strain S b when an avalanche is triggered. This energy is sometimes called the depinning energy, and in the framework of the pinning-depinning theory, several models predict Gaussian statistics [47][48][49][50]. In our case, unlike these models, we observe a power-law distribution, and the measured experimental exponent is close to 1: γ = −1.08 ± 0.1.…”
Section: A Global Avalanchessupporting
confidence: 39%
“…Heterogeneities of fracture energy in 3D brittle materials have been shown to lead to similar instabilities, producing the so-called crackling noise [7,17,18]. This effect was shown to increase considerably the macroscopic fracture energy of brittle disordered materials [19,20].…”
Section: (B) As a Function Of The Level Of Heterogeneity Dsmentioning
confidence: 99%
“…Unfortunately this approach gives the critical force only up to a numerical prefactor, whose value depends on microscopic quantities such as the geometrical shape of the impurities, and which is essential to determine in view of applications. Recently, a numerical self-consistent scheme [22,23] and numerical simulations have focused on a precise determination of the critical force [24,25] in the context of brittle failure. Notably, is has been shown that in the collective regime, occurring at weak disorder amplitude, the critical force does not depend on the disorder distribution but only on the disorder amplitude and correlation length [24].…”
Section: Introductionmentioning
confidence: 99%